Demystifying Modern Data Warehousing: From Traditional to Cloud-Native Solutions - Suresh Kumar Somayajula, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
The article explores the transformative landscape of cloud-native data warehousing, investigating the paradigm shift from traditional on-premises infrastructures to advanced cloud-based architectures. Through comprehensive analysis across diverse industry sectors, the study illuminates the profound technological and operational metamorphosis enabled by cloud data warehouse solutions. By examining performance metrics, resource utilization, security frameworks, and organizational capabilities, the article provides critical insights into how modern data management technologies transcend historical computational limitations. The article reveals substantial improvements in query processing, resource optimization, and governance capabilities, demonstrating cloud-native architectures' potential to revolutionize enterprise data strategies. Beyond technical advancements, the study elucidates the complex interplay between technological innovation and organizational adaptation, offering a nuanced understanding of cloud data warehousing's strategic implications.
Keywords: Cloud-Native Data Warehousing; Enterprise Analytics; Real-time Processing; Resource Optimization; Data Security Governance